2014
DOI: 10.1016/j.pedneo.2013.07.007
|View full text |Cite
|
Sign up to set email alerts
|

Epidemiology of Enterovirus 71 Infections in Taiwan

Abstract: Enterovirus 71 (EV71) was first described in USA in 1969 but retrospective studies in The Netherlands further detected EV71 in the clinical specimens collected in 1963. EV71 has one single serotype measured by using hyperimmune animal antisera but can be phylogenetically classified into three genogroups (A, B, and C) including 11 genotypes (A, B1-B5, C1-C5). In Taiwan, EV71 caused a large-scale nationwide epidemic in 1998. Retrospective studies further detected EV71 in clinical specimens collected from hand-fo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
39
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 56 publications
(40 citation statements)
references
References 44 publications
1
39
0
Order By: Relevance
“…Either the different virulence of different genotypes, host factors and other socioeconomic factors [13, 1922] may contribute to the severe complication and sequelae of EV71 infection as well.…”
Section: Discussionmentioning
confidence: 99%
“…Either the different virulence of different genotypes, host factors and other socioeconomic factors [13, 1922] may contribute to the severe complication and sequelae of EV71 infection as well.…”
Section: Discussionmentioning
confidence: 99%
“…50 Subgenogroups C2, C4 and B5 with genomic variations have repeatedly appeared during outbreaks in Japan between 1990 and 2013. 120 EV-A71 has caused nationwide epidemics in Taiwan 121 The C4 subgenotype emerged in 1998 in China with a predominance of the C4b lineage until 2009 followed by the exclusive occurrence of the C4a lineage until now. Between 2008 and 2014, C4 epidemics have been responsible for more than 10 million HFMD cases with a case-severity and case-fatality rates per year of 1.1% and 0.03-0.04%, respectively.…”
Section: Molecular Epidemiologymentioning
confidence: 99%
“…Sequential inter-genotype shifts from C2 to B4 and subsequently from C4 to B5 were observed in Taiwan. 7,121,126 The co-circulation of several EV-A71 genotypes and CV-A16 during HFMD epidemics has been responsible for intra-typic genetic recombination between EV-A71 B and C genotypes in Taiwan and inter-typic recombination between EV-A71 and CV-A16 in China. 5,7,14,19,126,129 Another inter-serotypic recombination happened between EV-A71 genotype C2 and CV-A8 to create genotype B4, responsible for outbreaks in Japan and Taiwan in 1998.…”
Section: Molecular Epidemiologymentioning
confidence: 99%
“…[3][4][5][6][7] In 1998, EV71 caused a large-scale epidemic in Taiwan, which led to 405 severe cases and 78 deaths due to the development of neurologic complications such as meningitis and encephalitis. [8][9][10] Despite the fact that EV71 causes fatal diseases, it has also been reported that it has diverse manifestations, ranging from asymptomatic, mild disease, to extremely severe disease to fatal deaths. 6 Genetic factors are believed to cause the differences in physical responses to the same virulence of pathogens, such as tumor necrosis factor, a promoter type II.…”
mentioning
confidence: 99%